ANALISIS FINANSIAL USAHA PEMBENIHAN IKAN NILA (Oreochromis niloticus) KELOMPOK PEMBUDIDAYA IKAN ALAM SUBUR DI DESA PURWAJAYA KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - Usup Ida; Helminuddin; Gusti Haqiqiansyah (2339-1324, 2021)
The study aimed at financially analyzing the business viability of Nile Tilapia (Oreochromis niloticus) hatchery by Alam Subur fish farmer group and analyzing the sensitivity level of Nile Tilapia (Oreochromis niloticus) hatchery business by Alam Subur fish farmer group against the economic variable changes in Purwajaya Village, Loa Janan Sub-district. Data collection from the field was conducted in December 2019; the primary data was collected by conducting a direct interview with the respondents using a list of questions made according to the research objective. Sampling was done using the census method and all population members (3 people) became the respondents. To know the business viability, the researcher conducted the financial analysis using the following indicators: NPV, IRR, Nen, and B/CPbP, and the sensitivity analysis to know the sensitivity level to both benefits and costs. The result of the analysis showed an NPV of 89.858.225, an IRR of 117%, an NBCR of 3.7, and a Payback Period of 1.35 years. Consequently, Nile Tilapia (Oreochromis niloticus) hatchery business by Alam Subur Fish Farmer Group in Purwajaya Village, Loa Janan Sub-district, was viable (profitable) and it can be maintained. The result of the sensitivity analysis showed that Nile Tilapia (Oreochromis niloticus) hatchery business by Alam Subur Fish Farmer Group in Purwajaya Village, Loa Janan Sub-district, was very sensitive to a decline in revenue and an increase in costs. Keywords: Alam Subur, Nile Tilapia Hatchery, Purwajaya Village